Influence of Scavenger on Abrasive Stability Enhancement and Chemical and Mechanical Properties for Tungsten-Film Chemical- Mechanical-Planarization. (22nd July 2020) - Seo, Eun-Bin; Bae, Jae-Young; Kim, Sung-In; Choi, Han-Eol; Kim, Pilsu; Lee, Jong-Chan; Son, Young-Hye; Yun, Sang-Su; Park, Jin-Hyung; Park, Jea-Gun
Abstract : In tungsten(W)-film chemical-mechanical-planarization(CMP), Fenton reaction between ferric-based-catalyst and oxidant hydrogen peroxide (H2 O2 ) enhances the chemical-oxidation degree of the W-film surface and degrades the abrasive stability of a W-film CMP-slurry as a trade-off effect. The addition of a scavenger (i.e., trilithium citrate tetrahydrate: TCT–Li) in the W-film CMP-slurry improved significantly the abrasive stability. A ionized scavenger (i.e., citrate ions) produced a Fe(III)-citrate complex and chemically reacted with the reactive radicals (i.e., OH ·, HO2 · and O2 ·− ), depressing Fenton reaction in a ferric-catalyst-based W-film CMP-slurry. Hence, the abrasive stability of the W-film CMP-slurry was improved with the scavenger concentration. In addition, TCT–Li influenced mainly the chemical properties such as the chemical-oxidation degree for the W-film surface and the hydrolysis degree of the SiO2 -film surface. Thus, the W-film polishing-rate slightly decreased with the scavenger concentration while the SiO2 -film peaked at a specific scavenger concentration (i.e., 0.1-wt%). In addition, two chemical reaction regions were found; i.e., the scavenger-concentration dominant chemical-reaction at the region I (i.e., TCT–Li 0 ∼ 0.1 wt%) and the catalyst [i.e., Fe(NO3 )3 ]-concentration dominant chemical-reaction at the region II (i.e., TCT–Li 0.1 ∼ 0.3 wt%). The region I showed more strongly a chemical-dominant-reaction than the region II, determining the W- and SiO2 -film polishing-rate.